Reclaiming Agency, Ensuring Survival: Disabled Urban Ghanaian Women's Negotiations of Church and Family Belonging - Nepveux, Denise M. (Disability Studies Quarterly, 2006)
This paper draws from a narrative ethnography of women members of disabled people's organizations (DPOs) in Accra, Ghana. Through recounting their autobiographical stories, elicited in multiple interviews, it explores how they navigate tensions among disability status, material survival, family belonging and religious participation Finding themselves neither fully acknowledged in family roles nor as religious community members, disabled women struggle to carve out spaces of self-determination and well-being between families and religious institutions, and between their developing aspirations and the circumscribed options available to them at the intersections of poverty, gender and disability. Women draw from multiple experiences, communities and discourses to interpret disability in complex and varied ways, not solely within the "moral models" often attributed to African cultures. Utilizing three biographical narratives from a 2003-2004 qualitative study, this paper shows how urban Ghanaian women with disabilities work to redefine themselves as social participants, and indeed as fully human, through engagement with religion. Implications for disability activism are discussed in the paper's conclusion.